Pengenalan Bahasa Isyarat Indonesia (BISINDO) Untuk Karakter Huruf Dengan Menggunakan Microsoft Kinect - Anton Breva Yunanda; Fridy Mandita; Aidil Primasetya Armin (Fountain of Informatics Journal, 2018)
Language is a tool used by humans to communicate between each others. Every human being was born in the world has the ability to communicate in accordance with his mother's language but not all humans are born with good communication skills, one of them is a person with special needs. Sign language is a communication device used by people in need a in communicating with other people. This language uses the body's members to communicate, one way to communicate is to use members of the body that is the hand. Every movement that is done will have a different meaning. In decades, the research in sign language is experiencing a very rapid development. In this study shows the introduction of sign language for character characters using Microsoft Kinect and the Hidden Markov Model (HMM) method. For data are taken from the (Bahasa Isyarat Indonesia) BISINDO dictionary. The results of this research is the level of accuracy of the introduction of letters.